Clinical Outcomes of Magnesium Sulphate and Aminophylline in Adult Acute Asthma: A Systematic Review and Network Meta-analysis - I Putu Angga Manik Pratama; Luh Gede Janny Resista Yani; Bagus Agung Arya Dharma Pramana Dwi Sutanegara; I Gede Arya Yoga Dharma Wiguna (Riviera Publishing, 2026)
Magnesium sulfate (MgSO?) and aminophylline are commonly used as adjunctive therapies in adults with acute asthma exacerbations who do not adequately respond to standard treatment. However, their comparative effectiveness remains uncertain. This network meta-analysis (NMA) aimed to evaluate the clinical outcomes of MgSO? and aminophylline in adults with acute asthma. A systematic review and meta-analysis were conducted following PRISMA guidelines, identifying articles from PubMed, SpringerLink, and Taylor & Francis. Random-effects models generated standardized mean differences (SMD) with 95% confidence intervals (CI). A league rank table was also generated to estimate the most effective agent in treating acute asthma. Overall heterogeneity was evaluated using the I² test. The NMA demonstrated no statistically significant difference between MgSO? and aminophylline in improving FEV? (SMD = 0.68; 95% CI: ?1.59 to 2.95; p = 0.5573). Ranking analysis suggested that, besides placebo, nebulized MgSO? had the highest probability of being the most effective intervention for FEV? improvement, although this finding did not reach statistical significance (nebulized MgSO?: MD = 1.11; 95% CI: 0.20–3.38; p = 0.6641). Qualitative synthesis indicated that MgSO? was associated with improvements in PEFR. In addition, aminophylline showed a potential reduction in hospital admission rates, whereas results for MgSO? were inconsistent across studies. MgSO? and aminophylline showed comparable effects on FEV? improvement in adults with acute asthma. MgSO? demonstrated favorable results in PEFR improvement, while aminophylline may offer potential benefits in reducing hospital admissions. Given the heterogeneity and limited sample sizes of available trials, further high-quality head-to-head studies are warranted to clarify their relative clinical effectiveness.